E-Agri: A Game-Changer for Indian Agriculture - Fatima Akther (PT FORMOSA CENDEKIA GLOBAL, 2023)
The paper examines the potential of e-agriculture in India, a rapidly developing nation with a large agricultural sector. It looks at the current state of e-agriculture in India and the opportunities and challenges faced by stakeholders in the sector. The study reviews the current initiatives taken by the government of India to promote e-agriculture and how these initiatives are impacting the agricultural sector. It also examines the effects of technology, such as the use of mobile phones and the internet, on the agricultural sector. The paper concludes by discussing the potential of e-agriculture in India and the need for further research in the area.